Germany's uncertain power: foreign policy of the Berlin Republic - Maull, Hanns W. (Palgrave Macmillan, 2006)
policy since 1998 / Peter Molt -- Business as usual : Red-Green policies toward Pacific Asia / Jörn-Carsten Gottwald -- Germany and the Iraeli-Palestinian conflict / Martin Beck -- Conclusion : uncertain power - German foreign policy into the twenty-first century / Hanns W. Maull
Includes bibliographical references and index
Keywords: Germany -- Foreign economic relations; Germany -- Foreign relations -- European Union countries; European Union countries -- Foreign relations -- Germany; Germany -- Foreign relations -- 1990-; Germany -- Military policy; Deutschland; USA; Aufsatzsammlung; Geschichte 1998-2005; Sicherheitspolitik; Außenpolitik; Geschichte 1990-2005